2012
DOI: 10.1007/s12094-012-0925-9
|View full text |Cite
|
Sign up to set email alerts
|

Competing causes of death in patients with locoregionally advanced head and neck cancer treated with concomitant boost radiation plus concurrent weekly cisplatin

Abstract: Patients with locoregionally advanced head and neck cancer treated with concomitant boost accelerated radiation plus chemotherapy show significant risks of mortality from causes other than disease progression.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 21 publications
0
11
0
Order By: Relevance
“…Disappointing long-term results of concomitant CRT deserve further evaluation and investigation since severe late toxicity following CRT is common in long-term survivors and a higher mortality from causes other than disease progression is reported in treated patients [43,46]. The development of more potent IC regimens may further improve patient outcomes.…”
Section: Larynx Preservationmentioning
confidence: 99%
“…Disappointing long-term results of concomitant CRT deserve further evaluation and investigation since severe late toxicity following CRT is common in long-term survivors and a higher mortality from causes other than disease progression is reported in treated patients [43,46]. The development of more potent IC regimens may further improve patient outcomes.…”
Section: Larynx Preservationmentioning
confidence: 99%
“…Various studies with long term tumour control and survival as end points have identified such cut-off values for PTV ranging from 19.6 cm 3 to 35 cm 3 and for TTV, from 22.8 cm 3 to 110 cm 3 depending upon the places where these were conducted. [13][14][15][16][17][18][19][20][21][22][23] In our study, for early response evaluation at 3 months of CCRT "optimal threshold cut-off" for PTV and TTV were higher (41 cm 3 and 42 cm 3 , respectively), primarily owing to a large tumour burden in our country. This method may categorise patients into either a favourable group (TV less than cut-off) or unfavourable group (TV more than cut-off) at a pre-treatment stage.…”
Section: Discussionmentioning
confidence: 65%
“…Impact of primary tumor volume on prognosis and prognostic "threshold cut-off" of primary tumor volume -all head and neck sites Locally advanced head and neck cancers have a poor prognosis. [24][25][26] With the rapid advancement in the delivery of RT and the rapidly emerging era of organ preservation, CCRT is well-established treatment modality in locally advanced head and neck cancers. It is important to determine the predictors for outcome in these patients who are to be treated with CCRT.…”
Section: Variability Of Tumor Volume Within Same T-staged Tumorsmentioning
confidence: 99%